GEOMETRIC PROBABILITY CALCULATION FOR A TRIANGLE - Aharonyan, N.G.; Harutyunyan, H.O. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In the paper, using a relationship between probability P(L(ω)D) that a random segment of length l in R^n having a common point with body D entirely lying in D and the covariogram of D, we obtain the explicit form of P(L(ω)D) for any triangle on the plane.